469 SACUBITRIL/VALSARTAN REDUCES CARDIAC DECOMPENSATION IN HEART FAILURE WITH PRESERVED EJECTION FRACTION: A SYSTEMATIC REVIEW AND META-ANALYSIS. (15th December 2022) - Carbone, Francesca; Basile, Christian; Marzano, Federica; Gargiulo, Paola; Guarnaccia, Teresa; Soriano, Simona; Simeoli, Luisa; Esposito, Gennaro; Monaco, Salvatore; Chieffo, Antonio; Perrone-filardi, Pasquale; Paolillo, Stefania
Abstract: Background: The impact of sacubitril-valsartan on heart failure patients with preserved ejection fraction (HFpEF) is uncertain. The purpose of this meta-analysis was to explore the clinical advantages and safety of sacubitril-valsartan in patients with HFpEF. Methods: PubMed and Web of Science were searched without any restrictions from inception to 08 May 2022 to identify valuable articles. The studies that met the inclusion criteria were analyzed. Results: Four trials, with a total of 7, 008 patients were included. Compared with valsartan, sacubitril-valsartan significantly reduced the rate of HF decompensation and of the combined endpoint of HF decompensation and all-cause mortality. All-cause mortality, NYHA class improvement and rate of hyperkalemia were not significantly different between the two groups. Regarding safety, sacubitril-valsartan was more likely to increase the risk of hypotension. Conclusion: This meta-analysis suggests that sacubitril-valsartan may be an effective strategy to reduce HF decompensation events in patients with HFpEF.